ANALISIS NILAI TAMBAH USAHA RUMAH TANGGA ASINAN CEMPEDAK DI DESA RIWA KECAMATAN BATU MANDI KABUPATEN BALANGAN - Mahdalena Mahdalena; Sri Roliani (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
This study aims to know the general picture effort household asinan cempedak in The Village Riwa District a Shower The County Balangan, knowing the magnitude of the value of added derived from the effort asinan cempedak in The Village Riwa District a Shower The County Balangan. This study was conducted on the effort of household manufacture asinan cempedak in The Village Riwa District a Shower The County Balangan. Methods used is a method census, methods collecting data and using the wawancara. Analysis used is analysis of the value of added tha using the hayami. The results of research obtained by the system of treatment effort asinan cempedak using the raw materials skin part in cempedak. The value of added derived from asinan cempedak is of Rp.59.660/kg. The value of added is obtained from the value output (production asinan cempedak) with the cost of the raw materials and the cost of supporting lannya. While the ratio value added asinan cempedak is of 59,07%, it means every one kilograms production asinan cempedak produce the value of 6%.